ACHIEVE THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM THROUGH THE INDEPENDENT TEACHING PLATFORM - Kurnia, Titim; Prawira, Kirana Qurotal Aini (Balai Diklat Keagamaan Bandung, 2024)
This study seeks to strike a balance between school program execution and teacher motivation, specifically the government's program to comprehend and implement the independent curriculum. The Indonesian Ministry of Education and Culture's independent teaching platform (PMM), which is implemented online, was also used to give teachers and schools with an awareness of the independent curriculum, which is a new curriculum in Indonesia. To collect research data, the study used a qualitative research approach, but for analysis, quantitative methods were used. As a result, the generated ordinal data is first converted into interval data for statistical inference analysis. Data sources are teachers who are not included in the driving teacher program. The investigation revealed various irregularities in the findings of the independent teaching platform (PMM) program. First, experienced and older teachers do better. However, it appears that this is not always relevant to the understanding and implementation of the independent curriculum. Second, teachers who are young in age and experienced are suspected of not performing well. However, it appears that they can also do adequately. Thus, the PMM program can be viewed as one that truly aids teachers in comprehending and implementing the independent curriculum.